Kebijakan Penanganan Pertambangan Emas Tanpa Izin (PETI) di Kabupaten Bungo - Didik Try Putra; Teguh Yuwono; Laila Kholid Alfirdaus (Ideas Publishing, 2023)
Bungo, one of the districts in Jambi Province, is currently rampant in PETI (Unlicensed Gold Mining). There are six sub-districts experiencing problems with unlicensed gold mining, namely Limbur Lubuk Mengkuang, Batin III Ulu, Tanah Tumbuh, Rantau Pandan, Pelepat Ilir, and Pelepat. The method used in this study is descriptive qualitative method. The results showed that the policy related to PETI (Unlicensed Gold Mining) in Bungo Regency has not been clearly determined, so there are still many illegal mining, and continue to expand without control from the government or official institutions. This is evidenced by the increasing number of dompeng machines and excavator heavy equipment owned by miners.